2021
DOI: 10.3892/etm.2021.10215
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates ischemic stroke injury in rats by protecting the integrity of the blood‑brain barrier

Abstract: The blood-brain barrier (BBB) is critical for proper cerebral homeostasis and its dysfunction during ischemic stroke can result in significant neurological injury. The major goal of the present study was to identify whether curcumin pretreatment possessed protective effects on BBB integrity during the 24 h of acute ischemic brain injury. To investigate the protective effects of curcumin, male Sprague-Dawley rats were divided into multiple groups, including sham, middle cerebral artery occlusion/reperfusion (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 50 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…TIMP1 and PLAUR have been identified in the previous studies as involved in the progression of ICH. Matrix metalloproteinases (MMPs) are the most important degrading enzymes in the pathogenesis of ICH ( 49 ), during extracellular matrix reconstruction and blood–brain barrier disruption ( 50 ). TIMP1 is a major endogenous inhibitor of MMP-9 and was found to be significantly more expressed in the serum of patients with ICH than in normal controls in a study of the Chinese Han patients with ICH ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…TIMP1 and PLAUR have been identified in the previous studies as involved in the progression of ICH. Matrix metalloproteinases (MMPs) are the most important degrading enzymes in the pathogenesis of ICH ( 49 ), during extracellular matrix reconstruction and blood–brain barrier disruption ( 50 ). TIMP1 is a major endogenous inhibitor of MMP-9 and was found to be significantly more expressed in the serum of patients with ICH than in normal controls in a study of the Chinese Han patients with ICH ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations in BBB regulation may contribute to the development of psychiatric disorders, including depression [ 119 121 ]. In vitro and animal studies have demonstrated that curcumin can protect the integrity of the BBB after ischemic stroke injury [ 122 ], cerebral ischemia-reperfusion injury [ 123 ], subarachnoid haemorrhage [ 124 ], and hypoxia [ 125 ].…”
Section: Curcumin’s Potential Antidepressant Mechanisms Of Actionmentioning
confidence: 99%
“…Numerous studies have explored the protective role and mechanism of action of curcumin on BBB after ischemic stroke. Curcumin can protect the integrity of BBB and reduce brain edema by the upregulation of aquaporin 4 and tight junction proteins such as zonula occluden 1 (ZO-1), occludin, and claudin-5, and the downregulation of matrix metalloproteinase 9 (MMP-9), intercellular adhesion molecule-l (ICAM-1), and vascular cell adhesion molecule-l (VCAM-1) ( Li et al, 2017 ; Wang et al, 2019a ; Wicha et al, 2020 ; Wu et al, 2021 ). Furthermore, curcumin attenuates cerebral capillary endothelial cell damage by inhibiting the expression of inducible nitric oxide synthase (iNOS) and the generation of NO(x) (nitrites/nitrates contents), thereby preventing BBB damage ( Jiang et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%